High metastatic tumor-derived CXCL16 mediates liver colonization metastasis by inducing Kupffer cell polarization via the PI3K/AKT/FOXO3a pathway - Yin Liu; Yunpeng Zhai; Yi Zhang; Liming Song; Hanyue Zhang; Jiahui Cao; Senfeng Zhao; Yahui Wu; Ruopeng Liang; Rongtao Zhu; Weijie Wang; Yuling Sun (Neoplasia: An International Journal for Oncology Research)
Liver metastases represent a late-stage manifestation of numerous cancers, often associated with poor patient prognosis. Kupffer cells (KCs), resident liver macrophages, play a critical role in liver metastasis (LM). However, the mechanisms by which the polarization of KCs facilitate colorectal cancer (CRC) liver metastases remain elusive. Here, we established a CRC liver metastasis mouse model and employed a co-culture system, found that KCs were recruited and polarized to M2 phenotype. We isolated and purified highly metastatic cell lines to reveal potential changes in CRC cells during metastasis. Through bulk RNA sequencing, we identified and validated CXCL16 as a positive mediator in liver-metastatic CT26-LM cells that induced an M2-like KC phenotype. Knock down of CXCL16 reduced the M2 polarization of KCs and inhibited the formation of liver metastasis lesions. Next, this polarization process was shown to be achieved through the PI3K/AKT/FOXO3a pathway. Further investigation revealed FOXO3a transcriptionally activates CD206(MRC1) in this process. Pharmacological inhibition of the CXCL16-PI3K-FOXO3a axis to disrupt the polarization of KCs attenuated CRC liver metastasis in vivo. Our findings collectively indicate that targeting the CXCL16/PI3K/AKT/FOXO3a pathway in KCs may represent a promising therapeutic strategy for preventing CRC liver metastasis.